eCM 2015
DOI: 10.22203/ecm.v029a21
|View full text |Cite
|
Sign up to set email alerts
|

A new concept for implant fixation: bone-to-bone biologic fixation

Abstract: Many attempts have been made to reduce complications of bone implant, such as pedicle screw loosening. To address this problem, the authors suggest a new concept of boneto-bone biologic fixation using recombinant human bone morphogenetic protein-2 (rhBMP-2)-loaded cannulated pedicle screws. Recombinant human bone morphogenetic protein-2 is an osteoinductive cytokine. Four types of titanium pedicle screws were tested (uncannulated, cannulated with no loading, beta-tricalcium phosphate (TCP)-loaded, and TCP/BMP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…we designed a novel biomimetic micro/nano-structured surface with surface roughness value exactly in this scale. Many reports have also manifested that the gradient biomimetic morphology would be beneficial in promoting cell adhesion, especially initial adhesion [57][58][59]. Beyond that, on the surfaces with nano-scale surface roughness, it is reported that osteoblasts had more available adhesion sites, proliferated and interacted more, which eventually resulted in positive effect on osteogenesis [60][61][62][63].…”
Section: In Vitro Cell Behaviormentioning
confidence: 99%
“…we designed a novel biomimetic micro/nano-structured surface with surface roughness value exactly in this scale. Many reports have also manifested that the gradient biomimetic morphology would be beneficial in promoting cell adhesion, especially initial adhesion [57][58][59]. Beyond that, on the surfaces with nano-scale surface roughness, it is reported that osteoblasts had more available adhesion sites, proliferated and interacted more, which eventually resulted in positive effect on osteogenesis [60][61][62][63].…”
Section: In Vitro Cell Behaviormentioning
confidence: 99%
“…Kim et al, [6] suggested a new concept of bone-to-bone biologic fi xation using recombinant human BMP-2 (rhBMP-2)-loaded pedicle screws.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the method of application bone morphogenetic protein (BMP-2)was greatly affects the osteoconductivity of dental implant surfaces. (8) used recombinant human bone morphogenetic protein-2 (rhBMP-2)-loaded pedicle screws to formulate a new hypothesis of bone-to-bone biologicallock .…”
mentioning
confidence: 99%
“…They concluded that the combination of coating implants with BMP-2 and VEGFcould enhance the bone volume density in the area surrounding the implants, although there was not Bone implant contact observed in this condition. , 2015) (8) used recombinant human bone morphogenetic protein-2 (rhBMP-2)-loaded pedicle screws to formulate a new hypothesis of bone-to-bone biological lock .…”
mentioning
confidence: 99%